Protective effects of Gyrinops versteegii leaf ethanol extract on Leydig cells and testosterone under excessive physical activity: an in vivo study - Widianti, I Gusti Ayu; Wardana, Nyoman Gede; Widhiartini, Ida Ayu Alit; Pratiwi, Made Sindy Astri; Antari, Ni Wayan Sukma (Universitas Muhammadiyah Purwokerto, 2026)
Background: Excessive physical activity may lead to overtraining syndrome and increased oxidative stress, which can reduce Leydig cell count and testosterone levels. Gaharu (Gyrinops versteegii) leaf ethanol extract contains strong antioxidants that may counteract oxidative damage. However, the effects of excessive physical activity on Leydig cells and testosterone remain unexplored. Purpose: This study aimed to evaluate the protective effects of Gyrinops versteegii leaf ethanol extract on male reproductive parameters under excessive physical activity conditions. Methods: This experimental study employed a randomized, post-test control-group design. Twenty-five adult male Wistar rats were divided into five groups: normal control, excessive physical activity control, and three treatment groups receiving Gyrinops versteegii leaf ethanol extract at 100, 200, and 400 mg/kg BW. Leydig cell counts and serum testosterone levels were analyzed using ANOVA and correlation tests. Results: The highest Leydig cell count and testosterone level were observed in the 200 mg/kgBW group (28.92 cells and 1.822 ng/mL, respectively). Significant differences in Leydig cell counts were observed among groups (p<0.001), and a positive correlation between Leydig cell number and testosterone levels was observed (p=0.006). Conclusion: Gyrinops versteegii leaf ethanol extract demonstrated protective effects against reproductive impairment induced by excessive physical activity in vivo, with an optimal dose of 200 mg/kgBW.